Determination of andrological and spermatological parameters in Southern Karaman breed rams under threat of extinction - Acisu, Tutku Can; Yuksel, Emine; Yilmaz, Tulay Canatan; Cihangiroglu, Aslihan Cakir; Badilli, Nida; Baykalir, Yasin; Simsek, Ulku Gulcihan (Univ Tripoli, Fac Vet Med, 2025)
Background: Agriculture and livestock breeding are industries that contribute significantly to national economies by providing basic food resources, supplying raw materials to the industrial sector, and creating a large employment area. In sheep breeding, which has an essential role in animal husbandry, the protection, production, and widespread use of local sheep breeds are crucial. In this respect, data on the spermatological properties of rams of the Southern Karaman breed are limited. Aim: This study aimed to determine the andrological and spermatological parameters of Southern Karaman rams. Methods: Morphometric measurements were initially conducted on the ram testicles as part of the andrological examination. In order to determine the spermatological characteristics, the volume, motility, and concentration of semen obtained with an electro-ejaculator were determined, and the ratios of dead, live, and abnormal spermatozoa were determined. Testosterone levels were measured by the ELISA method in blood samples taken from rams. Results: The average body weight of Southern Karaman breed rams was 63.80 f 4.12 kg. As a result of morphometric measurements, the mean right testis length, width, and thickness were 12.27 f 1.87, 5.47 f 0.59, and 6.16 f 0.68 cm, respectively, and the mean left testis length, width, and thickness were 12.37 f 1.91, 5.45 f 0.76, and 6.23 f 0.84 cm, respectively. The mean scrotum thickness was 0.38 f 0.03 cm, and the mean scrotum girth was 29.87 f 3.22 cm. It was measured as 724.28 f 156.18 ml mean testicular volume. The spermatological findings were evaluated; the average semen volume obtained from Southern Karaman rams was 0.64 f 0.22 ml, the average mass activity score (1-5) was 4.28 f 0.95, the average total motility value was 81.42% f 12.14%, the average semen concentration was 1688.57 f 429.24 x 106 sperm ml-1, the average viability rate was 79.00% f 3.26% and the average abnormal sperm rate was 3.85% f 1.21%. The average blood serum testosterone level was 4.91 f 0.74 ng/ml. Conclusion: There is insufficient information about the reproductive performance of Southern Karaman rams, which is an important but endangered breed specific to Turkey, and as a result of this study, testicular characteristics, spermatological, and hormonal characteristics of Southern Karaman rams were included them in the literature.
Keywords: Andrology; Endangered breed; Semen; Southern Karaman ram; Testicles